Sistem Temu Kembali Informasi Dinas Pemuda Olahraga dan Pariwisata Kabupaten Purbalingga dengan Metode Vector Space Model - Muhammad Syafiq Hidayatulloh (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
Tourism in Indonesia has now increased both natural and artificial tourism. In Indonesia there are very many tourism offerings ranging from land tourism to water. Purbalingga Regency can be said as agrowing regency, especially in the tourism sector and is starting to be made as a comparison with tourism in other cities in Central Java. Information Retrieval System is an optimization in searching websites so that users get information as expected. Tourism in Purbalingga Regency is still experiencing problems, namely aspects in providing detailed information on attractions. The use of the retrieval system is expected to be used as search optimization to improve the relevance of the query to the tourism documents in Purbalingga Regency. The limited information about tourism in Purbalingga is still lacking, resulting in tourists outside the area not knowing what tourism is in Purbalingga. The tools that will be used to create this information retrieval system are the Codeigniter framework then the programming language PHP for websites with data storage using the Mysql database. In the process of building the information retrieval system, an algorithm called vector space model is needed as a calculation of the relevance of the query to the document. The application of tourism information retrieval system in Purbalingga Regency is expected to help the condition of tourism in Purbalingga Regency to be improved, especially in tourism information. The results of this study are websites searcht hat will provide tourist attraction information in accordance with the query entered by the user and then display documents relevant to the query.